Halal Guarantee System for Bottled Drinking Water (AMDK) Production of Al-Falah Bangakalan Copontren in View of Has 23000 - Azzah Rahmalia Nabilah; Muttaqin Choiri; Muhammad Ersya Faraby (Values: Jurnal Kajian Islam Multidisiplin, 2024)
The need for halal products is very urgent at the moment, especially regarding Muslim consumers in Indonesia. In an effort to improve the Islamic boarding school economy, the government launched the "One Islamic Boarding School, One Product" (OPOP) program, to support halal products. Al-Falah Bangkalan Islamic Boarding School is working on the Islamic boarding school business, by producing Bottled Drinking Water (AMDK) under the Kepank brand. Even though water in fiqh is considered holy and halal, even though it has undergone a filtering process, it requires a halal test to make it safe for consumption, especially for Muslim consumers. This writing examines the implementation of the Halal Guarantee System (SJH) in Kepank AMDK products produced by the Al-Falah Islamic Boarding School, Bangkalan. According to incidents in the field, Islamic boarding schools do not pay attention to halal quality guarantees in accordance with HAS 23000. AMDK producers are starting to realize this need and are trying to implement SJH in every production.  This writing uses a descriptive qualitative method. Data collection techniques are taken from primary and secondary data. Data collection techniques were obtained from observation, interviews and documentation. The results of this writing show that the HAS that has been determined in HAS 23000; includes halal management, employee training, as well as halal processing and storage procedures that Kepank AMDK has met standardization, sterilization and components in HAS 23000 as a whole in the SJH process, Kepank AMDK is assisted in the certification process by the halal center of Madura Trunojoyo University and has received halal certification from BPJPH in 2024.